On analytical expressions for the distribution of the filtered output of square envelope receivers with signal and colored Gaussian noise input. - Monroy, I.T.
Closed-form expressions for the moment generating function (MGF) of the filtered output of square envelope receivers with signal and colored Gaussian noise input are derived. The informative signal is a binary sequence of rectangular pulses. The considered Gaussian processes are the Wiener process, a Gaussian process with linear covariance (moving average), and the Ornstein-Uhlenbeck process. The derived MGFs are then applied to the problem of finding the quantum limit for optically preamplified, direct detection receivers
Keywords: Gaussian processes; OOK receivers; Ornstein-Uhlenbeck process; Wiener process; Analytical expressions; Binary sequence; Closed-form expressions; Colored Gaussian noise input; Direct detection receivers; Filtered output distribution; Informative signal; Linear covariance; Moment generating function; Moving average; On-off keying; Optically preamplified receivers; Quantum limit; Rectangular pulses; Signal input; Square envelope receivers